The Postgraduate Medical Informatics Programme at the University of Cape Town - Hanmer, Lynn A. (Methods of Information in Medicine, 1989)
The Medical Informatics education programme at the University of Cape Town was developed as part of the postgraduate education programme run by the Department of Biomedical Engineering. The aim of the programme is twofold:a) To give students a broad background in Medical Informatics, to enable them to participate in the development, planning and management of information systems to support health care in South Africa, andb) To enable them to do a research project in a specialised area, thus learning research techniques, and contributing to the development of Medical Informatics as a discipline.Students benefit from participating in a postgraduate programme in a multidisciplinary department, which is firmly linked to the health care environment. A more specialised Medical Informatics programme is planned, but the multidisciplinary nature of work in this field will continue to be emphasised.
Keywords: Education; Curriculum; Medical Informatics